Comparative Health Assessments of Alaskan Ice Seals - Goertz, Caroline E. C.; Reichmuth, Colleen; Thometz, Nicole M.; Ziel, Heather; Boveng, Peter (Frontiers in Veterinary Science, 2019)
Bearded (Erignathus barbatus), ringed (Pusa hispida), spotted (Phoca largha), and ribbon (Histriophoca fasciata) seals rely on seasonal sea-ice in Arctic and sub-Arctic regions. Many aspects of the biology and physiology of these seals are poorly known, and species-typical health parameters are not available for all species. Such information has proven difficult to obtain due to the challenges of studying Arctic seals in the wild and their minimal historic representation in aquaria. Here, we combine diagnostic information gathered between 2000 and 2017 from free-ranging seals, seals in short-term rehabilitation, and seals living in long-term human care to evaluate and compare key health parameters. For individuals in apparent good health, hematology and blood chemistry values are reported by source group for 10 bearded, 13 ringed, 73 spotted, and 81 ribbon seals from Alaskan waters. For a smaller set of individuals handled during veterinary or necropsy procedures, the presence of parasites and pathogens is described, as well as exposure to a variety of infectious diseases known to affect marine mammals and/or humans, with positive titers observed for Brucella, Leptospira, avian influenza,  herpesvirus PhHV-1,  and morbillivirus. These data provide initial baseline parameters for hematology, serum chemistries, and other species-level indicators of health that can be used to assess the condition of individual seals, inform monitoring and management efforts, and guide directed research efforts for Alaskan populations of ice-associated seals.